Notices (Blackfriars, 1934)
The Protestant Reformation. By Joseph Clayton, F.R. Hist, S. The Lira of Cardinal Vaughan, By J. G. snead-Cox. Life of Mother Margaret Mary Hallahan. by Mother Francis Raphacl Drane, O.P. With a Preface by Archbishop Ullathorne and a Foreword to tlie Second Edition by the V. Rev. Fr. Bede Jarrett The Way of the King. By Father Martin Dempsey. Thoughts of Bl. Julie Billiart. Selected and Arranged for Every Day in the Year by a Sister of Notre Dame. Sparks beneath the Ashes. Experiences of a London Probation Officer. By Many Ellison. Oberammercau. Its History and its Passion Play. By lisabethe H. C. Corathiel. Wild Strawberries. A Novel by Angela Thirkell.